HUBUNGAN KUALITAS PELAYANAN ANTENATAL CARE (ANC) DENGAN TINGKAT KEPUASAN IBU HAMIL DI PUSKESMAS KARANGANYAR KABUPATEN PURBALINGGA TAHUN 2013 - Puji Rahayu, Lina Dwi; Fajarsari, Dyah; Mastuti, Sri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
ABSTRACT: THE CORRELATION BETWEEN THE QUALITY OF ANTENATAL CARE SERVICE AND THE PREGNANT WOMEN SATISFACTION LEVEL IN PUBLIC HEALTH CENTER OF KARANGANYAR PURBALINGGA 2013. The using of health facilities were barely maximised so far, it happened because of people were not fully satisfied with the health services provided by the local government. One of causes was the quality of health service run by the local government was not fulfill the society’s expectation. The research to find out the relationship between the quality of antenatal care service and the pregnant women satisfaction level in public health center of Karanganyar Purbalingga 2013. This research was a analytic-survey research with using the cross sectional approach. The samples of this research were the 74 pregnant women in public health center of Karanganyar Purbalingga 2013. Moreover, the data analysis method used in this research was using Rank Spearman method. 45 people or 60,8 % of people were feeling satisfied with the quality of antenatal care service. In other hand, the amount of pregnant women feeling satisfied was 52 people (70,3%). Therefore, based on that two results, I believed that there was a relation between the Antenatal Care service (ANC) with the pregnant women satisfaction (p = 0,000). In brief, based on the data’s result, there was relation between the Antenatal Care service (ANC) with the pregnant women satisfactory in public health center of Karanganyar Purbalingga 2013. Keywords: quality of service, satisfaction, Antenantal Care